ANALISIS ISI KURIKULUM PENDIDIKAN AGAMA ISLAM DI TADIKA AL FIKH ORCHARD MALAYSIA - Nanda Amelia Putri; Hasrian Rudi Setiawan (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2026)
This article aims to describe the content of the Islamic Education curriculum at Tadika Al Fikh Orchard Malaysia, identify the Islamic values applied in the curriculum, and assess the suitability of the Islamic Education curriculum at Tadika Al Fikh Orchard Malaysia with the developmental stages of students. The method used in this study was qualitative with a phenomenological research design. The data sources used in this study were divided into two types: primary and secondary data. The data collected in this study were obtained through observation, interviews, and documentation techniques. The collected data were then analyzed using an interactive model with descriptive analysis that provided a detailed description of the phenomenon under study. In this study, data validity was maintained through triangulation techniques. The results of this study indicate that the content of the PAI curriculum at Tadika Al Fikh Orchard Malaysia not only regulates cognitive achievements but also emphasizes the integration of faith, worship, and moral values through habitual activities and role models, and is structured according to the developmental stages of students. The results of this study deepen the understanding of the PAI curriculum as a dynamic value system, while also providing a basis for the development of an Islamic value-based curriculum model that can be applied in a relevant manner to Islamic educational institutions in the current era.